Digital Nudging in Accounting and Ethical Decision-Making - Winda Wulandari; Sri Widyastuti; Harnovinsah Harnovinsah; Rafrini Amyulianthy (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
This study examines the development of digital nudging research, with a focus on accounting and ethical decision-making. Using a systematic literature review guided by the PRISMA framework, 29 Scopus articles were analyzed. While the field has grown recently, digital nudging research remains fragmented, particularly in its ethical integration. The dominance of quantitative methods and nudge theory, along with a lack of interdisciplinary and contextual perspectives, signals persistent gaps. In accounting, digital nudging increasingly shapes professional judgment and ethical behavior. This study argues that closing these conceptual and methodological gaps and systematically integrating ethical and interdisciplinary insights is essential for advancing the field